PENGARUH KESESUAIAN KOMPENSASI, MORALITAS MANAJEMEN, DAN KEEFEKTIFAN PENGENDALIAN INTERNAL TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI PADA PERUSAHAAN KONSTRUKSI DI MANADO - Alou, Shelby Defiany; Ilat, Ventje; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2017)
Within the scope of accounting, the concept of fraud is a deviation from accounting procedures that should not be applied in an entity. Such delusions will have an impact on the financial statements presented by the company (Ariani, 2014). This study aims to examine the effect of conformity of compensation, management morality, and effectiveness of internal controls on the tendency of accounting fraud in employees of construction companies in Manado. The population in this study is a construction company in Manado. Sampling was done by purposive sampling which amounted to 4 companies. The sample of this research is 36 employees who work in the finance department at construction companies in Manado. The method of data analysis used is multiple linear regression analysis. The result of this research are: (1) compensation suitability has no effect on the tendency of accounting cheating on employees of construction companies in Manado; (2) management morality has no effect on the tendency of accounting fraud in employees of construction companies in Manado; (3) the effectiveness of internal controls has a positive and significant effect on the tendency of accounting cheating on construction company employees in Manado.Keywords: Compensation Compliance, Management Morality, Effectiveness of Internal Control, Accounting Fraud Trend